2023
DOI: 10.1002/ptr.7872
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV ameliorates radiation‐induced nerve cell damage by activating the BDNF/TrkB signaling pathway

Abstract: Radiation can induce nerve cell damage. Synapse connectivity and functionality are thought to be the essential foundation of all cognitive functions. Therefore, treating and preventing damage to synaptic structure and function is an urgent challenge. Astragaloside IV (AS‐IV) is a glycoside extracted from Astragalus membranaceus (Fisch.). Bunge is a widely used traditional Chinese medicine in China with various pharmacological properties, including protective effects on the central nervous system (CNS). In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…As a natural compound, AS-IV has been identified as having antiradiation, antioxidation, antiinflammation, ant-hypertension, antiapoptosis, and other effects ( 28 , 29 ). Our previous studies suggest that AS-IV can substantially reduce the apoptosis and senescence of brain cells under IR exposure ( 16 , 17 ). Interestingly, recent studies have shown that AS-IV can exert a protective role by regulating mitophagy ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a natural compound, AS-IV has been identified as having antiradiation, antioxidation, antiinflammation, ant-hypertension, antiapoptosis, and other effects ( 28 , 29 ). Our previous studies suggest that AS-IV can substantially reduce the apoptosis and senescence of brain cells under IR exposure ( 16 , 17 ). Interestingly, recent studies have shown that AS-IV can exert a protective role by regulating mitophagy ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…AS-IV with a purity >98% was obtained from Dalian Meilun Biotechnology Co., Ltd. (Dalian, China), DMSO was purchased from Solarbio (Beijing, China), and CsA was purchased from AbMole Bioscience Inc (Houston, TX, USA). The AS-IV dosages were selected based on previous studies ( 16 , 17 ). After 1 month of administration, Cobalt-60 ( 60 Co) radiation (Lanzhou Weite Radiation Co., Ltd., Lanzhou, China) was used in mice, and the cumulative radiation dose was 8 Gy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation